Penerapan Teori Sosial Kognitif Karir pada Bimbingan Karir dalam Upaya Membantu Pengambilan Keputusan Karir - Faizatul Khasanah; Ni’matin Muyassaroh; Muhamad Rifa’i Subhi (Universitas Lampung, 2020)
This article explores the notion of the cognitive social theory of careers. The social theory of cognitive careers is a theory about a career that adopts the behavioral theory of bandura to take a career decision. The purpose of the social in this theory is the client's expectations of career decisions taken, while the intent of cognitive is the belief of the client. To help one's career decision making can be done by using a career's social cognitive theory, because this theory can assist clients in developing, transforming, teaching the careers that their clients demand. This theory also relates to self efficacy, ie individual beliefs about his ability to perform tasks or actions necessary to achieve certain results. This article focuses on individuals who are still in their early adolescence. The career guidance done by the author succeeds in assisting clients in making career decisions in accordance with the client's belief. The client decides to make a career as a doctor, the client is sure to be able to live his career well because the client has a lot of experience in the field of medicine.Keywords: social cognitive social theory, career decision making, early adolescence, career guidande resultsDOI: http://dx.doi.org/10.23960/jiip.v2i1.21813